Expanding the reproductive organ phenotype of CHD7‐spectrum disorder. Issue 5 (16th February 2023) - Nomakuchi, Tomoki T.; Danowitz, Melinda; Stewart, Blythe; Leonard, Jacqueline; Izumi, Kosuke; Krantz, Ian; Kolon, Thomas F.; Langdon, David; Skraban, Cara; Van Batavia, Jason; Zackai, Elaine; Jiao, Kai; et al.
Abstract: CHD7 disorder is a multiple congenital anomaly syndrome with a highly variable phenotypic spectrum, and includes CHARGE syndrome. Internal and external genital phenotypes frequently seen in CHD7 disorder include cryptorchidism and micropenis in males, and vaginal hypoplasia in females, both thought to be secondary to hypogonadotropic hypogonadism. Here, we report 14 deeply phenotyped individuals with known CHD7 variants (9 pathogenic/likely pathogenic and 5 VOUS) and a range of reproductive and endocrine phenotypes. Reproductive organ anomalies were observed in 8 of 14 individuals and were more commonly noted in males (7/7), most of whom presented with micropenis and/or cryptorchidism. Kallmann syndrome was commonly observed among adolescents and adults with CHD7 variants. Remarkably, one 46, XY individual presented with ambiguous genitalia, cryptorchidism with Müllerian structures including uterus, vagina and fallopian tubes, and one 46, XX female patient presented with absent vagina, uterus and ovaries. These cases expand the genital and reproductive phenotype of CHD7 disorder to include two individuals with genital/gonadal atypia (ambiguous genitalia), and one with Müllerian aplasia.